In vitro growth of the bromeliad Alcantarea imperialis (Carrière) Harms with different concentrations of nitrogen - Kurita, Flavia Maria Kazue; Tamaki, Vivian (Acta Scientiarum. Biological Sciences, 2014)
In various ecosystems, many plants have been reduced in number or even eliminated from natural habitats, including the endangered ornamental romeliadAlcantareaimperialis(Carrière) Harms. Thein vitro cultureisatool thathas beenusedforconservationof endangered species andwidely usedfor the production ofornamental plants. This study aimed at investigating the influence of different nitrogen concentrations on the growth of plantlets of the bromeliad A. imperialis grown in vitro. Seedlings of A. imperialis were cultured on Murashige and Skoog medium, upplemented with different concentrations of nitrogen (0.00, 3.75, 7.50, 15.00, 30.00, 60.00, 90.00, 120.00, and 175.00 mM) at 30 mmol m-2 s-1, at 12 hour photoperiod and 26±2°C for six months. The results showed that plants grown with 15.00 and 60.00 mM N showed the best growth.